The evolution of separate sexes in waterhemp is associated with surprising chromosomal diversity and complexity. - Julia M Kreiner; Jacob S Montgomery; Marco Todesco; Natalia Bercovich; Yunchen Gong; Cassandra Elphinstone; Patrick J Tranel; Loren H Rieseberg; Stephen I Wright (PLoS Biology)
The evolution of separate sexes is hypothesized to occur through distinct pathways involving few large-effect or many small-effect alleles. However, we lack empirical evidence for how these different genetic architectures shape the transition from quantitative variation in sex expression to distinct male and female phenotypes. To explore these processes, we leveraged the recent transition of Amaranthus tuberculatus to dioecy within a predominantly monoecious genus, along with a sex-phenotyped population genomic dataset, and six newly generated chromosome-level haplotype phased assemblies. We identify a ~3 Mb region strongly associated with sex through complementary SNP genotype and sequence-depth-based analyses. Comparative genomics of these proto-sex chromosomes within the species and across the Amaranthus genus demonstrates remarkable variability in their structure and genic content, including numerous polymorphic inversions. No such inversion underlies the extended linkage we observe associated with sex determination. Instead, we identify a complex presence/absence polymorphism reflecting substantial Y-haplotype variation-structured by ancestry, geography, and habitat-but only partially explaining phenotyped sex. Just over 10% of sexed individuals show phenotype-genotype mismatch in the sex-linked region, and along with observation of leakiness in the phenotypic expression of sex, suggest additional modifiers of sex and dynamic gene content within and between the proto-X and Y. Together, this work reveals a complex genetic architecture of sex determination in A. tuberculatus characterized by the maintenance of substantial haplotype diversity, and variation in the expression of sex.